2017
DOI: 10.1590/1806-9061-2017-0537
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Commercial Laying Hen Submitted to Different Debeaking Methods

Abstract: Among the several factors required in breeding laying hens, debeaking is a factor that interferes with batch performance and affects animal welfare. Thus, the objective of this study was to evaluate three different debeaking procedures and to verify the best technique to be used. For this, the performance of the birds, the incidence of cannibalism, and in rearing phase, the quality of the eggs were evaluated. Dekalb White birds were distributed in a completely randomized design with three treatments, T1 (infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Research about stocking density and debeaking effects in cages showed improvement in egg production and lower decreased when increasing available area per bird (Oka et al, 2017). In the present study, because higher and lower densities did not affect (p>0.05) most performance para- meters, egg quail production with density up to 237.5 cm²/bird could be recommended.…”
Section: Discussionmentioning
confidence: 62%
“…Research about stocking density and debeaking effects in cages showed improvement in egg production and lower decreased when increasing available area per bird (Oka et al, 2017). In the present study, because higher and lower densities did not affect (p>0.05) most performance para- meters, egg quail production with density up to 237.5 cm²/bird could be recommended.…”
Section: Discussionmentioning
confidence: 62%
“…Vieira Filho et al (2016) obtained similar results when evaluating infrared and conventional debeaking, describing higher weights in infrared beak trimmed birds. Oka et al (2017) compared infrared and conventional methods and found better body development in infrared radiation debeaked birds. Dennis and Cheng (2010) investigated the characteristics related to production and stress in birds subjected to both beak trimming methods and noted infrared debeaking consists in a more welfare-friendly method, directly or indirectly improving body development and production.…”
Section: Discussionmentioning
confidence: 99%
“…Beak trimming is widely practiced in the poultry industry (Gonçalves et al, 2010;Oka et al, 2017), usually twice, with the first one being done between eight and 10 days of life, and the second one between eight and 10 weeks of age. Generally, the first debeaking is deeper, in a 2-4mm spacing between the cut and the bird's nostrils, and the second cut is generally is 5-8mm spaced.…”
Section: Introductionmentioning
confidence: 99%